Religious Epistemologis: Evidentialisme dan Eksklusivisme Humanist - Muliadi Muliadi (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2020)
This article seeks to explain about the spiritual model as an effort that is passed and taken by humans in understanding and achieving Something Absolute, namely God. The method used is reflective analysis, which describes deeply and comprehensively the potential inherent in human beings that is used in understanding the existence of self and God. Human definitions are very diverse, including: socio-political beings, thinking beings, sentient beings, even godly beings. All of these definitions reinforce that humans are creatures. While the object sought by humans is something that is outside and inside him. In its search, humans exploit the potential of knowledge inherent in themselves, starting from the simplest with empirical experience, then rationalist knowledge, to religious-spiritualist knowledge. With the perfection of potential and knowledge achieved, human beings are placed in two functions that must not be broken, namely to strengthen their pertical and horizontal relationships. This pertikal relationship is a form of exclusivity with his Lord, while his horizontal form is sincere dedication because he is with his fellow humans and his nature.